A köles (Panicum miliaceum L.) mint gyomnövény szerepe a gabonavírusok epidemiológiájában - Henézi, Ágnes; Pásztor, György; Takács, András Péter (GEORGIKON FOR AGRICULTURE, 2017)
The millet (Panicum miliaceum) is one of the oldest cultivated palnts. It was mentioned as weed in 1948–1961 near Bábolna by Fekete (1963). New Panicum species might appear and spread in the near future. The aim of experiment was virus infection of the millet as weed in the plough-land and the millet’s role in spreading of the most important cereal viruses. Natural virus infection in common millet (Panicum miliaceum) in surroundings of Keszthely and Lesencefalu was surveyed in September 2014 and 2015. The cereal viruses was tested by DAS ELISA serological methods. Among the 45 collected leaf samples 19 gave positive results. 10 Wheat streak mosaic virus (WSMV), 6 Wheat dwarf virus (WDV), 6 Barley stripe mosaic virus (BSMV), 2 Barley yellow dwarf virus (BYDV) and 1 Brome streak mosaic virus (BstMV) infestations were observed. Brome mosaic virus (BMV) was not detected in the investigated plants. Three WDV and WSMV, and only one WDV, WSMV and BYDV complex infections were identified. Our result indicate that millet as weed can play a role in the epidemiology of different cereal viruses.